Social Knowledge Facilitates Chunking in Infancy. Issue 4 (16th January 2014) - Stahl, Aimee E.; Feigenson, Lisa
<x xml:space="preserve">Abstract</x> Two experiments investigated whether infants can use their rich social knowledge to bind representations of individual objects into larger social units, thereby overcoming the three‐item limit of working memory. In Experiment 1, 16‐month‐olds (n = 32) remembered up to four hidden dolls when the dolls had faced and interacted with each other in pairs, but not when they faced and interacted with the infant, suggesting that infants chunked the dolls into social pairs. In Experiment 2 (n = 16), infants failed to remember four dolls when they faced each other without interacting, indicating that interaction between the dolls was necessary to drive chunking. This work bridges a gap between social cognition and memory by demonstrating that infants can use social cues to expand memory.